PENGEMBANGAN GAME INTERAKTIF WORDWALL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI THAHARAH DI SMPN PURWODADI - Ayunda Serly; Lia Nur Atiqoh B.D; Qurroti A’yun (VICRATINA, 2022)
This studies aims to develop and design an interactive wordwall game learning medium for Islamic religious education thaharah topics in Purwodadi SMPN. The type of research used is research and development with the ADDIE development model. This research was carried out with the aim of developing interactive wordwall game learning media in taharah topic, knowing the effectiveness of interactive wordwall game learning media in thaharah material and seeing the responses of students to the wordwall interactive game learning media. The results of the validation of media to media experts obtained an average percentage of media learning feasibility of 85.3% with a very feasible category. The media validation results for materials experts obtained an average media learning feasibility percentage of 86% with a very feasible category. The effectiveness of wordwall interactive game learning media is seen in the percentage of completion of students to work on the questions. The percentage of compliance obtained by the students is 80% with a good category. Student responses to wordwall interactive game learning media are divided into two small-scale and large-scale. Small-scale student responses earn a mean percentage score of 78.8% in the appropriate category. On the other hand, the answers of the students on a large scale obtain an average percentage score of 88.1% with a very feasible category